DISPUTE SETTLEMENT BETWEEN INDONESIA AND SOUTH KOREA (Allegations of Dumping Practice by Indonesia on Paper Products) - Raditya Permana; Maya Ruhtiani (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
This research entitled Dispute Settlement Between Indonesia and South Korea (Allegation of Dumping Practice by Indonesia on Paper Product) aims to analyze the dispute settlement between Indonesia and South Korea on the allegations of dumping practice. The research method is Juridical Normative. Indonesia is one of the WTO members which have ratified the Agreement Establishing the WTO by Law Number 7 in 1994. It means that Indonesia is a subject to the provisions of the WTO including the provisions on anti-dumping disputes. On 30 September 2002, Indonesia and South Korea were involved in the import duty case of anti-dumping paper products. It was occurred when a South Korean paper industry proposed anti-dumping petitions against Indonesian paper products to the Korean Trade Commission (KTC). The Indonesian paper products are charged with dumping including 16 products which belong to the group of uncoated paper and paper board used for writing, printing, or other graphic purpose and carbon paper, self-copy paper and other copying.